2016
DOI: 10.1016/j.seizure.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of active convulsive epilepsy in an urban slum in Enugu South East Nigeria

Abstract: Purpose To determine the prevalence of active convulsive epilepsy and treatment gap in two Urban slums in Enugu South East Nigeria. Methods A 3 phase cross-sectional descriptive study was done to survey individuals ≥15 years in 2 slums in Enugu, South East Nigeria. Results The prevalence of epilepsy was 6.0 (95% CI: 5.9–6.0) per 1000 (men 4.4/1000, 95% CI: 2.3–6.4, women 7.8/1000, 95% CI: 4.9–10.4), p = 0.06. The peak age of active convulsive epilepsy was 40–44 years (11.2 per 1000) with two smaller peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 24 publications
3
28
2
Order By: Relevance
“…Burial of PWE far away from home prevents people from getting epilepsy. Eating, sleeping together or wearing same clothes with PWE is said to be a source of infection [43,44]. Eating of pork by someone with epilepsy promotes cysticercosis and corroborates with a study that found a significant link between cysticercosis occurrence and epilepsy [78].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Burial of PWE far away from home prevents people from getting epilepsy. Eating, sleeping together or wearing same clothes with PWE is said to be a source of infection [43,44]. Eating of pork by someone with epilepsy promotes cysticercosis and corroborates with a study that found a significant link between cysticercosis occurrence and epilepsy [78].…”
Section: Discussionsupporting
confidence: 68%
“…Also included are protozoon and helminthic infections, including admission to hospital with malaria, exposure to T. c a n i s , T. gondii, O. volvulus and T. s o l i u m [40] of which Taenia solium has received attention in sub-Saharan Africa over the past few years. Neurocysticercosis is a common cause of epilepsy in pig breeding area [76], however the wide variation in the frequency of epilepsy in the continent could be due to different definitions and type of epilepsy including the population studied and type of sample [44]. Some studies in the region showed the association between epilepsy and cysticercosis using different diagnostic criteria both for epilepsy and cysticercosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient's/ caregiver's beliefs about epilepsy may expose them to stigmatizing factors and environments [23]. With a prevalence of epilepsy ranging between 4.3-6 per 1000 and low levels of knowledge and practice of epilepsy in urban and sub urban areas in south east Nigeria [24,25], enacted stigma is expected to be a common experience among PWE. Understanding of stigmatization in epilepsy and its correlates is relevant to the understanding of the burden of epilepsy in Sub Saharan Africa (SSA).…”
Section: Introductionmentioning
confidence: 99%